Sustainability certification among smallholders in Malaysia: a review / Nurul Shazleen Mustaffa Kamall - Mustaffa Kamall, Nurul Shazleen (Faculty of Plantation and Agrotechnology, 2019)
This study attempts to identify the current status among smallholders on sustainability certification in Malaysia and to anticipate the sustainability certification adoption among smallholders namely organized and independent smallholders. The inputs were obtained from a few existing literature available in database example Web of Science (WoS), Scopus and Google Scholar resources identified related 57 studies. This study focuses on adoption of smallholders towards sustainability certification. The result shows that the organized smallholder are more engaged in willingness to comply the certification standards towards sustainable palm oil production, meanwhile it is creating a lot of challenges that the independent smallholders experiences mainly regard their knowledge, financial incentives, experience of organization, external support and certification cost. In conclusion, organized smallholder are major in willingness to participate into certification schemes and in comparison, many of the challenges for independent smallholder certification centrals around the adoption of agricultural changes, the acceptance of new practices and the changing of habits.